(untitled) - Bryman, Alan (Oxford, 2011)
Business Research Methods is a practical and comprehensive guide for business and management students embarking on research projects. The authors, along with students and supervisors, draw on their own experiences so that students can take note of real-world professional tips for success and avoid making common mistakes. Each chapter is filled with examples that provide context for the theories and concepts being discussed.
Keywords: Kinh doanh,Business; Nghiên cứu,Phương pháp luận,Methodology,Research